Examine the Obstacles to RME Implementation with the PIECES Method Based on the User's Perspective - Prisusanti, Retno Dewi; Rusfadir, Agustina; Reliubun, Nabila Marshufa Salim (PT FORMOSA CENDEKIA GLOBAL, 2024)
Karel Sadsuitubun General Hospital, similar to numerous other healthcare facilities, has adopted RME. Implementing RME is essential for enhancing the effective and efficient management of risks. The approach employed in this study is qualitative description with an emphasis on case studies. Data were gathered via semi-structured, in-depth interviews involving three informants: TPPRJ officers, TPPRI, and reporting officers. Employing purposive sampling, the interviews explored six aspects, revealing seven key points concerning obstacles encountered in implementing RME at Karel Sadsuitubun Hospital. These barriers include RME system performance, system speed, features in the RME system, accuracy of system information, data integrity, technical constraints, resources and financing systems, and data security in the system. The implementation of the RME system in this hospital still faces various problems such as system performance, system speed, data integrity, technical constraints, resources and financing systems, and data security.